Role of the World Bank in developing agricultural research in India - Gautam, Madhur; Jenane, Chakib; Adjato, Ramziath (Indian Farming, 2018)
India’s agricultural research system has evolved over the years to become one of the largest and widely recognized national agricultural research system in the world, shaped by strong commitment and consistent financial support from the Government of India. The World Bank has been a consistent partner through this evolution. This system has achieved impressive results, most notably in the form of the Green Revolution and national food security, that have paved the way to positioning India as a major agricultural power house. Notwithstanding these achievements, India’s agricultural research system can not rest on past or current achievements but must continue to evolve to address unprecedented challenges facing Indian agriculture, as well as to help it to fully exploit emerging opportunities. The research agenda going forward will be considerably more complex than in the past, involving a slowdown in productivity growth, climate change and depleting natural resources, consumers demand for quality products and food safety across the value chain, in addition to nutritional security and reducing poverty. These new challenges require innovative thinking and most importantly a reorientation of R&D towards more efficient and sustainable use of natural resources and rematching of needs with resources.